BUDAYA DIGITAL REMAJA INDONESIA: DOMINASI INSTAGRAM DAN TREN KONSUMSI KONTEN DIGITAL - Hidayat, Nurul; Halim, Umar (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
In recent years, Instagram has dominated the social media activities of Indonesian teenagers, while meme content has become increasingly popular as a form of digital entertainment. In line with this phenomenon, this study aims to describe the intensity of Instagram usage and consumption trends of meme content among Indonesian teenagers. This study uses a quantitative descriptive survey method involving 337 teenagers aged 10-20 years as respondents. The results show that among Indonesian teenagers, the frequency of Instagram access is very high, averaging more than six times per day with a duration of use exceeding four hours per day. In addition, meme content is the most frequently accessed type of content; around 73.2% of respondents frequently consume meme content. In conclusion, Instagram dominates the daily digital activities of Indonesian teenagers, underscoring the platform's central role in youth digital culture. Memes have also emerged as a major trend in digital content consumption among teenagers.